Comparative Efficiency of Daihy Plants in the States of Haryana and Rajasthan - Ahuja, Usha Rani (Annals of Arid Zone, 2016)
Comparative efficiency of the dairy plants of Haryana and Rajasthan based on turn over ratios, computed at constant and current prices (1970-84), have been studied. For whole of H.D.D.C.F. (Haryana) capital productivity turned out to be 55 percent at constant and 49 per cent at current prices. Capital productivity was maximum (74 percent at constant and 67 percent at current prices) for Jind milk plant. The capital productivity for whole of R.C.D.F. (Rajasthan) was 40 percent at constant and 38 percent at current prices. Capital productivity was maximum (93 percent at constant and 89 per cent at current prices) for Bikaner plant. In case of labour productivity. output per employee was found to be more than 26 thousand rupees at constant and almost double at current prices. Jind in H.D.D.C.F. and Bikaner in R.C.D.F. were most resource efficient plants.